Political Dominance of the Nobles in the Golkar Party of Bone Regency - Putra, Muhammad Amril Pratama; Hartaman, Nursaleh (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2022)
The purpose of this research was to find out how the political dominance of the noble descendants in the Golkar party of Bone Regency. The research method used is qualitative with several research indicators processed through nvivo12 plus application. The results showed that the political dominance of noble descendants (Andi) on the Golkar party body has been going on for a long time, the existence of noble descendants is seen in the Chairman of DPD II Golkar Bone Regency occupied by noble descendants since 1971 - 2024. The dominance was born because the descendants of nobles had the good capacity and popularity in political contestation. Golkar party in cadre recruitment is open to all circles and does not distinguish from social strata, in the era of democracy there are no more restrictions to process in political parties. So actually there is no requirement to have a noble title to enter the party